Global and local genetic diversity at two microsatellite loci in Plasmodium vivax parasites from Asia, Africa and South America - Schousboe, M.L.; Ranjitkar, S.; Rajakaruna, R.S.; Amerasinghe, Priyanie H.; Konradsen, Flemming; Morales, Francisco José; Ord, R.; Pearce, R.; Leslie, T.; Rowland, M.; Gadalla, N; Bygbjerg, C.; et al. (Springer, 2014)
Background: Even though Plasmodium vivax has the widest worldwide distribution of the human malaria species and imposes a serious impact on global public health, the investigation of genetic diversity in this species has been limited in comparison to Plasmodium falciparum. Markers of genetic diversity are vital to the evaluation of drug and vaccine efficacy, tracking of P. vivax outbreaks, and assessing geographical differentiation between parasite populations._x000D_ Methods: The genetic diversity of eight P. vivax populations (n = 543) was investigated by using two microsatellites (MS), m1501 and m3502, chosen because of their seven and eight base-pair (bp) repeat lengths, respectively. These were compared with published data of the same loci from six other P. vivax populations._x000D_ Results: In total, 1,440 P. vivax samples from 14 countries on three continents were compared. There was highest heterozygosity within Asian populations, where expected heterozygosity (He) was 0.92-0.98, and alleles with a high repeat number were more common. Pairwise FST revealed significant differentiation between most P. vivax populations, with the highest divergence found between Asian and South American populations, yet the majority of the diversity (~89%) was found to exist within rather than between populations._x000D_ Conclusions: The MS markers used were informative in both global and local P. vivax population comparisons and their seven and eight bp repeat length facilitated population comparison using data from independent studies. A complex spatial pattern of MS polymorphisms among global P. vivax populations was observed which has potential utility in future epidemiological studies of the P. vivax parasite.